Strength power and technique of swimming performance: Science meets practice - Toussaint, H. M. (Schwimmen: Lernen und Optimieren, 27: Zur Methodik des Schwimmtrainings, Heft 3, 2007)
Peak performances in swimming require the full deployment of all powers a swimmer possesses. The development of those powers require years of hard training. Developments of measurement technology (e.g. MAD-system (Toussaint et al, 1988)) have aided the sport scientist in identifying several factors äs determinants of performance. These include drag, propulsion technique, and mechanical power (Toussaint & Truijens, 2005). Swimming fast will depend on 1. the ability to produce a high mechanical power Output enabling the generation of high propulsive forces, 2. the ability to reduce drag, while 3. keeping power losses to pushed away water (Pk) low, i.e.. swimming with a high propulsive efficiency. The development of this knowledge provides the modern swimming coach with some guide-lines how to design training programmes. However, it may be argued that training-time will be especially efficient when devoted to the enhancement of those performance factors that are weak links in the individual performance chain. This assumes that the right appropriate training equipment is used. In this paper special attention will be paid to the role strength training has in the practice of swim training and a sketch will be given how training can be linked to improvement in performance such that optimization of the training process becomes possible.